Maternal and child factors associated with diarrhea among children under five: A cross-sectional study - Elwan Chandra (Indonesian Journal of Health Services, 2026)
Background: Diarrhea remains an important cause of morbidity among children under five and is influenced by caregiver practices, infant feeding, infection exposure, and nutritional vulnerability. This study examined the associations of maternal knowledge, diarrhea-prevention practices, exclusive breastfeeding history, and child nutritional status with diarrhea among children aged 6-59 months in Sukajadi Urban Village, Ogan Komering Ulu Regency, Indonesia. Methods: An analytical cross-sectional study involved 113 mother-child pairs. Diarrhea was defined from caregiver report as three or more loose or watery stools within 24 hours during the preceding two weeks. Maternal knowledge and preventive practices were assessed using a structured questionnaire, exclusive breastfeeding history was obtained by caregiver report, and nutritional status was classified using weight-for-age. Associations were evaluated using prevalence ratios and robust Poisson regression. Results: The draft analytical values contained in the source manuscript classify 39 of 113 children (34.5%) as having diarrhea. Poor maternal knowledge, inadequate preventive practices, non-exclusive breastfeeding, and undernutrition were associated with higher diarrhea prevalence in the reported draft analyses, with inadequate preventive practices showing the largest adjusted association. These numerical results require verification against the original dataset before submission. Conclusion: The reported pattern suggests that maternal knowledge and preventive practices, breastfeeding history, and nutritional status are relevant correlates of childhood diarrhea in this local primary-care setting. Integrated Posyandu education, household hygiene support, breastfeeding counseling, growth monitoring, and targeted home visits may strengthen prevention.